Rheology of drugs for topical and transdermal delivery - Walicka, Anna; Falicki, Jarosław; Iwanowska-Chomiak, Beata (Zielona Góra: Uniwersytet Zielonogórski)
Skin drug delivery systems are a constant source of interest because of the benefits that they offer to overcome many drawbacks associated with other modes of drug delivery (i.e. oral, intravenous, etc.). Because of the impermeable nature of the skin, designing a suitable drug delivery vehicle that penetrates the skin barrier is challenging.
Keywords: drug delivery; human skin; drug rheology; rheological models